2021
DOI: 10.1002/1348-9585.12217
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of vitamins/antioxidants on occupational noise-induced hearing loss: A systematic review

Abstract: Objectives Occupational noise‐induced hearing loss (NIHL) due to industrial, military, and other job ‐related noise exposure can cause harmful health issues to occupied workers, but may also be potentially preventable. Vitamins/antioxidant have been studied as therapeutic strategies to prevent and/or delay the risks of human diseases as well as NIHL .So, this study was conducted to systematically review the protective effects of vitamins/antioxidants on occupational NIHL. Methods Online databases including Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Similarly, Kopke et al found that antioxidants help in reducing hearing damage after exposure to intense noises [23]. Studies have also suggested the association of vitamins B9 (folate) and B12 with HL [24]. A healthy diet rich in many nutrients may provide protection against HL through several mechanisms, including regulation of oxidative stress, protection of cochlear blood flow, reduction of neuroinflammation, and neurodegeneration of auditory nerve fibers and central auditory pathways [25].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Kopke et al found that antioxidants help in reducing hearing damage after exposure to intense noises [23]. Studies have also suggested the association of vitamins B9 (folate) and B12 with HL [24]. A healthy diet rich in many nutrients may provide protection against HL through several mechanisms, including regulation of oxidative stress, protection of cochlear blood flow, reduction of neuroinflammation, and neurodegeneration of auditory nerve fibers and central auditory pathways [25].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is associated with many forms of acquired hearing loss and antioxidants have therefore been considered as potential prophylactic drugs particularly in the context of noise-induced hearing loss (30,31). Despite overall promising preclinical data, many trials have been abandoned due to a lack of efficacy in humans (31). Antioxidants are likely to counteract the acute phase of ROS production leading to oxidative stressmediated unspecific damages.…”
Section: Discussionmentioning
confidence: 99%
“…Also, vitamin B12, folic acid, and NAC may have a protective effect on reducing occupational NIHL. 9 Furthermore, studies have shown that magnesium and minerals have the prophylactic effects in reducing the NIHL. 16,17 Our results showed the effect of vitamin A consumption in reducing NIHL.…”
Section: Discussionmentioning
confidence: 99%
“…8 Vitamins B9 (folate) and B12 have also been studied to be associated with hearing loss. 9 A healthy diet rich in many nutrients may be protective against hearing loss by several mechanisms, including regulating oxidative stress, protecting cochlear blood ow, and reducing neuroin ammation and neurodegeneration of auditory nerve bers and central auditory pathways. 10 Although previous research has shown how NIHL is associated with various risk factors, its association with dietary factors has not been investigated in population-based studies.…”
Section: Introductionmentioning
confidence: 99%